Use of natural sorbent for stormwater treatment - Valentukevičienė, Marina; Najafabadi, Maryam Ebrahimian (International Conference “Environmental Engineering”, 2020)
Stormwater runoff is an important avenue for pollutant transport from impermeable surfaces to surface waters. Consequently, stormwater pollutions require additional treatment processes to achieve water quality goals. Natural sorbents have been demanded and studied for using in water treatment because of their low cost and safety. In this study the use of Acorus Calamus, row Hemp, and procedure Hemp in stormwater treatment was investigated. Results of study in all sorbents with different concentrations and dosage indicated high efficiency to reduce pH. The use of Acorus Calamus for Turbidity, Phosphorus, conductivity and colour resulted increasing amount in different Dosage. In another experiments, using row Hemp, procedure Hemp and Linseed as natural sorbents indicated high efficiency to reduce turbidity of stormwater. Also it is obtained that procedure Hemp has high efficiency to reduce conductivity of stormwater.
Keywords: Hemp; stormwater; natural sorbent; water quality